Long‐term outcome of sacral nerve stimulation for faecal incontinence. (1st November 2020) - Leo, C. A.; Thomas, G. P.; Bradshaw, E.; Karki, S.; Hodgkinson, J. D.; Murphy, J.; Vaizey, C. J.
Abstract: Aim: Sacral nerve stimulation (SNS) is a minimally invasive treatment for faecal incontinence (FI). We report our experience of patients who have undergone SNS for FI with a minimum of 5 years' follow‐up. This is a single centre prospective observational study with the aim to assess the long‐term function of SNS. Method: All patients implanted with SNS were identified from our prospective database. The date of implantation, first and last clinic follow‐up, surgical complications and St Mark's incontinence scores were abstracted and analysed. Results: From 1996 to 2014, 381 patients were considered for SNS. Of these, 256 patients met the study inclusion criteria. Median age at implantation was 52 years (range 18–81). The ratio of women to men was 205:51. Indications were urge FI (25%), passive FI (17.9%) and mixed FI (57%). The median of the incontinence score at baseline was 19/24 and this improved to 7/24 at the 6‐month follow‐up. Of the total cohort, 235 patients received a medium‐term follow‐up (median 110 months, range 12–270) with a median continence score of 10/24 which was also confirmed at the telephone long‐term follow‐up on 185 patients (132 months, range 60–276). Conclusion: This study demonstrates that SNS is an effective treatment in the long term. SNS results in an improvement of validated scores for approximately 60% of patients; however, there is a significant reduction of efficacy over time due to underlying causes.